Clinical Phenotype of Diabetic Peripheral Neuropathy and Relation to Symptom Patterns: Cluster and Factor Analysis in Patients with Type 2 Diabetes in Korea - Jong Chul Won; Yong-Jin Im; Ji-Hyun Lee; Chong Hwa Kim; Hyuk Sang Kwon; Bong-Yun Cha; Tae Sun Park (Journal of Diabetes Research)
Objectives. Patients with diabetic peripheral neuropathy (DPN) is the most common complication. However, patients are usually suffering from not only diverse sensory deficit but also neuropathy-related discomforts. The aim of this study is to identify distinct groups of patients with DPN with respect to its clinical impacts on symptom patterns and comorbidities. Methods. A hierarchical cluster analysis and factor analysis were performed to identify relevant subgroups of patients with DPN (n=1338) and symptom patterns. Results. Patients with DPN were divided into three clusters: asymptomatic (cluster 1, n=448, 33.5%), moderate symptoms with disturbed sleep (cluster 2, n=562, 42.0%), and severe symptoms with decreased quality of life (cluster 3, n=328, 24.5%). Patients in cluster 3, compared with clusters 1 and 2, were characterized by higher levels of HbA1c and more severe pain and physical impairments. Patients in cluster 2 had moderate pain levels but disturbed sleep patterns comparable to those in cluster 3. The frequency of symptoms on each item of MNSI by “painful” symptom pattern showed a similar distribution pattern with increasing intensities along the three clusters. Conclusions. Cluster and factor analysis endorsed the use of comprehensive and symptomatic subgrouping to individualize the evaluation of patients with DPN.